Factores que Componen el Clima Organizacional en la Empresa Inversiones Alis Ltda. de Villavicencio (2013)
The company INVESTMENTS ALIS Ltda., that devotes itself to works of civil engineering, for 30 years was consolidated as one of the best companies of the sector delivering quality and sustainability. Today the management of this company, it affirms that his company has lost positioning in the market and his organization presents symptoms of lack of belonging, motivation, cooperation between the members and leadership, which they finish for affecting the climate organizacional. The boards of this company, they feel completely worried by the lack of motivation with which his collaborators work, situation that has led to the company is employed at a tense environment because there is no cooperation between the parts and with the time the deterioration becomes worrying in the labor behavior of his collaborators. In addition there has met affected the relation of the members of the company and the lack of motivation to achieve satisfactory results. The authors, bearing the study of the climate in mind organizacional it is fundamental to identify, to measure and to evaluate the action of the individual and the organization, they acquired the commitment to elaborate a plan of improvement of the same one for the company, by means of a descriptive investigation of type, using as instrument of compilation a survey (in two formats), the first one directed to diagnosing the labor climate of the company; and the second one of evaluation of the code of ethics fruit of this investigation.